Perceptions of females participating in a perceived ‘masculine sport’ : dragon boat - Vijaikumar Rangabashayam (2014)
Over the past several decades, the role of females in modern society has expanded and changed considerably. Nevertheless, stereotyping of women, particularly in areas such as Sport, still exists today. Therefore, the perceptions of female athletes participating in a perceived ‘masculine’ sport - Dragon Boat, will be examined by determining the effects of gender (male vs. female) and athletic identity (athlete vs. non-athlete) on these perceptions. The Athletic Identity Measurement Scale (AIMS) will be used to determine the athletic identity of 100 male and 100 female participants. Subsequently, the Bem Sex-Role Inventory (BSRI) will be used to calculate the Masculinity scores, which indicate the extent to which a person associates masculine characteristics to some given pictures depicting females participating in Dragon Boat. All participants were above 21 years of age and data collected was analyzed using Statistical Package for the Social Sciences (SPSS). The results suggested that gender is a factor in the perception of female athletes participating in Dragon Boat. However, male and female participants who considered themselves athletic did not perceive these females as portraying masculine traits. Male and female participants who consider themselves as Non-Athletic and all male participants perceived that females participating in Dragon Boat are masculine. Therefore, the Athletic Identity of an individual is a relevant factor in the perception of female athletes participating in Dragon Boat. These findings lead to the discussion of potential barriers posed by the perceptions on females participating in the sport of Dragon Boat. Additionally, the implications and directions for possible future research will also be discussed.